2020
DOI: 10.1155/2020/8864572
|View full text |Cite
|
Sign up to set email alerts
|

Dental Tissue-Derived Human Mesenchymal Stem Cells and Their Potential in Therapeutic Application

Abstract: Human mesenchymal stem cells (hMSCs) are multipotent cells, which exhibit plastic adherence, express specific cell surface marker spectrum, and have multi-lineage differentiation potential. These cells can be obtained from multiple tissues. Dental tissue-derived hMSCs (dental MSCs) possess the ability to give rise to mesodermal lineage (osteocytes, adipocytes, and chondrocytes), ectodermal lineage (neurocytes), and endodermal lineages (hepatocytes). Dental MSCs were first isolated from dental pulp of the extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
111
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(112 citation statements)
references
References 119 publications
(165 reference statements)
0
111
0
1
Order By: Relevance
“…Right next to the dental carie, periodontitis is a frequent disease of the periodontium complex, including gingiva, cementum, periodontal ligaments, and alveolar bone, traditionally treated by surgical means and guided tissue regeneration, with limited results [ 130 ]. In terms of periodontal regeneration based on dental MSCs, DPSCs, PDLSCs, SCAP, and DFSCs were taken into consideration for several studies [ 120 , 131 ]. For example, local injection of SCAP improved gingival attachment and enhanced bone and cementum regeneration [ 130 ].…”
Section: Experimental Therapeutic Applications Of Oral Mscs In Oramentioning
confidence: 99%
See 1 more Smart Citation
“…Right next to the dental carie, periodontitis is a frequent disease of the periodontium complex, including gingiva, cementum, periodontal ligaments, and alveolar bone, traditionally treated by surgical means and guided tissue regeneration, with limited results [ 130 ]. In terms of periodontal regeneration based on dental MSCs, DPSCs, PDLSCs, SCAP, and DFSCs were taken into consideration for several studies [ 120 , 131 ]. For example, local injection of SCAP improved gingival attachment and enhanced bone and cementum regeneration [ 130 ].…”
Section: Experimental Therapeutic Applications Of Oral Mscs In Oramentioning
confidence: 99%
“…Tissue engineering for periodontal tissue regeneration respects the same direction as for the endodontics diseases: stem cells therapy, scaffold supported strategy combined with growth factors, extracellular vesicles (exosomes) with conditioned medium [ 131 , 133 , 134 ].…”
Section: Experimental Therapeutic Applications Of Oral Mscs In Oramentioning
confidence: 99%
“…MSCs were reported to be present in the human teeth and supporting tissues, and these have been reported to be promising sources of MSCs [ 9 , 10 , 11 ]. These “Dental MSCs” are divided into several subpopulations, depending on their anatomical and histological origins.…”
Section: Introductionmentioning
confidence: 99%
“…MSCs have also been identified in the dental papilla located at the root apex of the developing permanent teeth and in the dental follicle of the developing tooth germs [ 15 , 16 , 17 ]. These subpopulations appear to share several qualities as MSCs, but their phenotypes and tissue regenerative potentials are not completely consistent [ 9 , 10 , 11 ]. Further investigations are required to define the differential phenotypes and tissue regenerative potentials in these subpopulations, particularly in MSCs associated with developing tooth germs.…”
Section: Introductionmentioning
confidence: 99%
“…MBMSCs and iliac MSCs have comparable osteogenic differentiation potential; however, MBMSCs have a weaker potential to differentiate to chondrocytes and adipocytes because of their different stem properties [ 8 , 9 ]. MBMSCs have been a candidate cell source for bone regenerative medicine in the maxillofacial region [ 10 ], and several bone regeneration studies using MBMSCs have been reported [ 11 , 12 ]. The population of plating bone marrow cells is heterogeneous; some MBMSCs have progenitor properties and multi-potent differentiation capacity, whereas others are devoid of this capacity [ 13 ].…”
Section: Introductionmentioning
confidence: 99%